A high-porosity dry-process diaphragm for lithium-ion batteries and a preparation method thereof

By using a dry separator with three-layer symmetric structure of A/B/A, the raw material composition and pore size design are adjusted, the problem of insufficient thickness and mechanical strength of lithium-ion battery separator when improving porosity is solved, and higher lithium ion transmission is achieved Efficiency and battery safety.

CN118712660BActive Publication Date: 2025-02-11NINGBO CHANGYANG TECH +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411178553.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2025-02-11
Estimated Expiration
2044-08-27

AI Technical Summary

Technical Problem

While improving porosity, existing lithium-ion battery separators are difficult to maintain sufficient thickness and mechanical strength, resulting in the inability to effectively reduce the internal resistance of the battery and the safety is threatened.

Method used

The dry diaphragm with three-layer symmetric structure is adopted. By adjusting the raw material composition and pore size design of each layer, combined with the addition of functional additives, the lithium ion transmission efficiency and mechanical properties of the diaphragm are improved.

Benefits of technology

On the premise of ensuring the safety of the diaphragm, the porosity and mechanical properties of the lithium-ion battery separator are significantly improved, the internal resistance of the battery is reduced, and the needs of many fields such as energy storage and power are met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the field of lithium battery separators, discloses a high porosity dry-process separator for lithium ion batteries and a preparation method thereof, using A / B / A three-layer symmetrical structure; A layer raw material includes long-chain branched polypropylene, nucleator a, polyurethane powder; B layer raw material includes: maleic anhydride modified high crystallinity polypropylene, nucleator b, glass fiber; nucleator a is selected from dimethyl diphenyl bisaminomethane, phenylacetone, phenyl propylene, terephthalimide, p-methoxyphenyl benzoic acid, one or more of pullulan; nucleator b is selected from talc, corundum, silicon dioxide, nano clay, hydroxylated phenol phosphate, sorbitol acetal, titanium dioxide one or more. The present invention is designed by adjusting and optimizing the raw material composition of each layer, so as to improve the lithium ion transmission efficiency of the separator and improve the mechanical properties of the separator under the premise of ensuring the safety of the separator.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium battery diaphragms, and in particular to a high-porosity dry-process diaphragm for lithium ion batteries and a preparation method thereof. Background Art

[0002] Lithium-ion batteries are mainly composed of positive electrodes, negative electrodes, electrolytes and diaphragms, among which the diaphragm plays a vital role in the battery. The diaphragm materials used in lithium-ion batteries are currently mainly composed of polyolefins as the main component. In the actual use of batteries, they have two main functions: one: to isolate the positive and negative electrodes of the battery to prevent short circuits; the other: to act as a channel to ensure the free passage of lithium ions and achieve rapid transmission of lithium ions between the positive and negative electrodes. Under the premise of ensuring these two major functions, the current production and actual use have put forward new requirements for the manufacture of diaphragms. Under the premise of ensuring basic functions, in order to control the internal resistance of the battery, it is hoped that the diaphragm will be as thin as possible, and the porosity needs to be increased as much as possible to provide more ion transmission channels to reduce the internal resistance of the battery.

[0003] However, in the existing industrial production, the increase in porosity means sacrificing thickness or mechanical strength. Without sufficient thickness, film formation may not occur during the preparation process, which directly affects the normal production of the product. The sacrifice in mechanical properties may lead to a decrease in puncture performance, which may even cause direct contact between the two poles of the battery and cause a short circuit, which makes the safety of the battery not guaranteed.

[0004] The patent with publication number CN116387757A discloses "a high-porosity sodium-ion battery stretching membrane and its preparation method", which adopts a three-layer structure, with a larger pore structure on the surface layer to accommodate more electrolyte, and a uniform and dense pore structure in the middle layer, which improves the transmission efficiency of sodium ions without sacrificing strength, and can simultaneously meet the requirements of power batteries, energy storage batteries and other fields for membrane safety. However, because it needs to meet the transmission requirements of sodium ions with larger ion radius, the improvement of porosity is still limited. When used in lithium-ion battery membranes, the internal resistance of the battery cannot be effectively reduced. Summary of the invention

[0005] The present invention aims to overcome the above-mentioned problems existing in the lithium-ion battery separators of the prior art, and provides a high-porosity dry-process separator for lithium-ion batteries and a preparation method thereof. The separator adopts a three-layer symmetrical structure, and the raw material composition of each layer is adjusted and optimized, and the pore size of the separator is designed. Thus, the lithium ion transmission efficiency of the separator is improved while ensuring the safety of the separator, and the mechanical properties of the separator are improved, which can simultaneously meet the requirements for excellent performance of lithium-ion battery separators in multiple fields such as energy storage and power.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A high-porosity dry-process separator for lithium-ion batteries, adopting an A / B / A three-layer symmetrical structure; in parts by weight, the raw materials of the A layer include: 80-95 parts of long-chain branched polypropylene, 1-10 parts of nucleating agent a, and 4-10 parts of polyurethane powder; the raw materials of the B layer include: 80-95 parts of maleic anhydride-modified high-crystallinity polypropylene, 1-10 parts of nucleating agent b, and 4-10 parts of glass fiber;

[0008] In the high-crystallinity polypropylene modified with maleic anhydride, the mass ratio of maleic anhydride to high-crystallinity polypropylene is 1-5:100, and the crystallinity of the high-crystallinity polypropylene is 60-70%.

[0009] The nucleating agent a is selected from one or more of dimethyldiphenylbisaminomethane, phenylacetone, phenylpropylene, terephthalimide, p-methoxyphenylbenzoic acid, and pullulan; the nucleating agent b is selected from one or more of talc, corundum, silicon dioxide, nanoclay, hydroxyphenol phosphate, sorbitol acetal, and titanium dioxide.

[0010] The present invention uses long-chain branched polypropylene as the matrix material in the surface layer (layer A), and adds nucleating agent a and polyurethane powder. Compared with ordinary linear polypropylene, long-chain branched polypropylene has higher melt strength, which can make the diaphragm have high porosity and good mechanical properties. The nucleating agent a in the present invention is a specific type of β nucleating agent. Adding it to the long-chain branched polypropylene can promote the formation of β lamellae. A sufficient number of β lamellae can be converted into α lamellae under the action of tensile stress in the subsequent stretching stage. The mesopores formed by this crystal transformation will have a significantly increased pore size, forming sufficiently dense and large pore size mesopores in the surface layer, so that the pore ratio can be increased without over-increasing the stretching ratio, and the porosity of the diaphragm can be increased, thereby providing more transmission channels. The added polyurethane powder is dispersed in the polymer matrix, which can enhance the structural rigidity and strength, thereby improving the puncture resistance of the diaphragm, and the polyurethane has a low thermal conductivity coefficient, which can enhance the thermal stability of the diaphragm at high temperatures.

[0011] The present invention adopts maleic anhydride modified high crystallinity polypropylene as the matrix material in the middle layer (layer B), and adds nucleating agent b and glass fiber. By changing the polarity of polypropylene through maleic anhydride grafting modification, and cooperating with a specific type of α nucleating agent b, the formation of α lamellae during the crystallization process can be regulated, thereby realizing the formation of small-diameter mesopores and even micropores during the stretching process, forming large-diameter mesopores in the surface layer, and forming small-diameter mesopores and micropores in the middle layer, which can effectively improve the porosity of the diaphragm without affecting its mechanical properties. In addition, grafting polar groups on the high crystallinity polypropylene matrix can enhance the adhesion between the diaphragm and the positive and negative electrode materials and improve the wettability between the diaphragm and the electrolyte; the properties of high crystallinity polypropylene itself can also give the diaphragm sufficient mechanical properties. The added glass fiber is interwoven in its structure to improve its mechanical stability, which is conducive to the improvement of its puncture performance, and the good elastic modulus of the glass fiber can improve its tensile resistance when it is used in the diaphragm.

[0012] Through the above-mentioned design of the pore size and the addition of functional additives, the present invention can increase the porosity of the diaphragm to 60-70% while ensuring the safety of the diaphragm, thereby improving the lithium ion transmission efficiency and mechanical properties of the diaphragm, and can simultaneously meet the requirements for excellent performance of lithium-ion battery diaphragms in multiple fields such as energy storage and power.

[0013] Preferably, the long-chain branched polypropylene is prepared by melt polymerization of trimethylolpropane trimethacrylate, alkyl mercaptan, initiator and polypropylene, the mass ratio of trimethylolpropane trimethacrylate, alkyl mercaptan and initiator is 1-2:1-2:1, the mass ratio of the total mass of trimethylolpropane trimethacrylate, alkyl mercaptan and initiator to polypropylene is 25-35:100; the weight average molecular weight of polypropylene is 100,000-150,000. The present invention uses alkyl mercaptan as a chain transfer agent, and trimethylolpropane trimethacrylate and polypropylene are melt polymerized to prepare long-chain branched polypropylene under the action of the initiator, which can improve the rheological properties and processability of polypropylene, so that it has better mechanical properties and processing characteristics.

[0014] Preferably, the alkyl mercaptan is selected from one or more of n-butyl mercaptan, 2,3-butanedithiol, 1,8-octanedithiol, cyclohexanethiol, dodecyl mercaptan, and n-tetradecyl mercaptan; and the initiator is dibenzoyl peroxide.

[0015] Preferably, the particle size of the polyurethane powder is 150-250 μm.

[0016] Preferably, when the nucleating agent is an inorganic nucleating agent, the particle size is 50 to 150 μm.

[0017] Preferably, the thickness is 12-25 μm, the thickness of layer A is 20-30% of the total thickness, and the thickness of layer B is 40-60% of the total thickness.

[0018] Preferably, the porosity is 60-70%, the air permeability is not greater than 230 s / 100 mL, the puncture performance is greater than 600 gf, the tensile strength in the MD direction is greater than 200 MPa, and the tensile strength in the TD direction is greater than 20 MPa.

[0019] The present invention also discloses a method for preparing the above-mentioned high-porosity dry-process diaphragm for lithium-ion batteries, comprising the following steps:

[0020] (1) Preparation of long-chain branched polypropylene and high-crystalline polypropylene modified with maleic anhydride;

[0021] (2) Casting sheet: The raw materials of the surface layer and the middle layer are mixed in proportion and then subjected to three-layer co-extrusion, and then pulled and cooled to obtain a casting sheet;

[0022] (3) Stretching film formation: The obtained cast sheet is subjected to heat treatment, longitudinal cold stretching, longitudinal hot stretching, and heat setting in sequence to obtain the high-porosity dry-process diaphragm for lithium-ion batteries.

[0023] Preferably, the method for preparing the maleic anhydride modified high crystallinity polypropylene in step (1) is: melt-extruding maleic anhydride, high crystallinity polypropylene and a free radical initiator to obtain the maleic anhydride modified high crystallinity polypropylene;

[0024] The preparation method of long-chain branched polypropylene is as follows: trimethylolpropane trimethacrylate, alkyl mercaptan and initiator are mixed and dissolved in an organic solvent, and then evenly sprayed on the surface of polypropylene pellets; the polypropylene pellets are dried, and melt polymerization is performed after the organic solvent is completely volatilized to obtain the long-chain branched polypropylene.

[0025] Preferably, in step (2), the extrusion temperature of the three-layer co-extrusion is 200-240° C., the cooling temperature is 80-100° C., and the pulling speed is 40-80 m / min.

[0026] Preferably, in step (3), the heat treatment temperature is 110-150°C, the heat treatment time is 10-30h, the longitudinal cold stretching temperature is 50-100°C, the stretching ratio is 1.2-1.5, the longitudinal hot stretching temperature is 140-170°C, the stretching ratio is 1.5-3.0, the heat setting temperature is 130-140°C, the stretching ratio is 0.8-1, and the heat setting time is 1-10min.

[0027] Therefore, the present invention has the following beneficial effects:

[0028] (1) Long-chain branched polypropylene is used as the matrix material in the surface layer, and a nucleating agent a is used to form sufficiently dense and large-diameter mesopores in the surface layer, thereby increasing the pore ratio without increasing the stretching ratio too much, thereby increasing the porosity of the diaphragm; the polyurethane powder added to the surface layer can improve the puncture resistance of the diaphragm and its thermal stability at high temperatures;

[0029] (2) In the middle layer, high-crystallinity polypropylene modified with maleic anhydride is used as the matrix material, and combined with a nucleating agent b, small-diameter mesopores or even micropores can be formed in the middle layer, which can effectively improve the porosity of the diaphragm without affecting its mechanical properties. DETAILED DESCRIPTION

[0030] The present invention is further described below in conjunction with specific implementation methods.

[0031] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments, unless otherwise specified, are conventional methods in the art.

[0032] Overall embodiment:

[0033] A high-porosity dry-process separator for lithium-ion batteries, adopting an A / B / A three-layer symmetrical structure; in parts by weight, the raw materials of the A layer include: 80-95 parts of long-chain branched polypropylene, 1-10 parts of nucleating agent a, and 4-10 parts of polyurethane powder; the raw materials of the B layer include: 80-95 parts of maleic anhydride-modified high-crystallinity polypropylene, 1-10 parts of nucleating agent b, and 4-10 parts of glass fiber;

[0034] In the high-crystallinity polypropylene modified with maleic anhydride, the mass ratio of maleic anhydride to high-crystallinity polypropylene is 1-5:100, and the crystallinity of the high-crystallinity polypropylene is 60-70%.

[0035] The nucleating agent a is selected from one or more of dimethyldiphenylbisaminomethane, phenylacetone, phenylpropylene, terephthalimide, p-methoxyphenylbenzoic acid, and pullulan; the nucleating agent b is selected from one or more of talc, corundum, silicon dioxide, nanoclay, hydroxyphenol phosphate, sorbitol acetal, and titanium dioxide.

[0036] As a specific implementation manner, the long-chain branched polypropylene is prepared by melt polymerization of trimethylolpropane trimethacrylate, alkyl mercaptan, initiator and polypropylene, the mass ratio of trimethylolpropane trimethacrylate, alkyl mercaptan and initiator is 1-2:1-2:1, and the mass ratio of the total mass of trimethylolpropane trimethacrylate, alkyl mercaptan and initiator to polypropylene is 25-35:100; the weight average molecular weight of polypropylene is 100,000-150,000.

[0037] As a specific implementation, the alkyl mercaptan is selected from one or more of n-butyl mercaptan, 2,3-butanedithiol, 1,8-octanedithiol, cyclohexanethiol, dodecyl mercaptan, and n-tetradecyl mercaptan; and the initiator is dibenzoyl peroxide.

[0038] As a specific implementation, the particle size of the polyurethane powder is 150-250 μm.

[0039] As a specific implementation, when the nucleating agent is an inorganic nucleating agent, the particle size is 50-150 μm.

[0040] As a specific implementation manner, the thickness is 12-25 μm, the thickness of layer A is 20-30% of the total thickness, and the thickness of layer B is 40-60% of the total thickness.

[0041] As a specific implementation, the porosity is 60-70%, the air permeability is not greater than 230 s / 100 mL, the puncture performance is greater than 600 gf, the tensile strength in the MD direction is greater than 200 MPa, and the tensile strength in the TD direction is greater than 20 MPa.

[0042] The present invention also discloses a method for preparing the above-mentioned high-porosity dry-process diaphragm for lithium-ion batteries, comprising the following steps:

[0043] (1) Preparation of long-chain branched polypropylene and high-crystalline polypropylene modified with maleic anhydride;

[0044] (2) Casting sheet: The raw materials of the surface layer and the middle layer are mixed in proportion and then subjected to three-layer co-extrusion, and then pulled and cooled to obtain a casting sheet;

[0045] (3) Stretching film formation: The obtained cast sheet is subjected to heat treatment, longitudinal cold stretching, longitudinal hot stretching, and heat setting in sequence to obtain the high-porosity dry-process diaphragm for lithium-ion batteries.

[0046] As a specific embodiment, the preparation method of the maleic anhydride modified high crystallinity polypropylene in step (1) is: melt-extrude maleic anhydride, high crystallinity polypropylene and a free radical initiator to obtain the maleic anhydride modified high crystallinity polypropylene;

[0047] The preparation method of long-chain branched polypropylene is as follows: trimethylolpropane trimethacrylate, alkyl mercaptan and initiator are mixed and dissolved in an organic solvent, and then evenly sprayed on the surface of polypropylene pellets; the polypropylene pellets are dried, and melt polymerization is performed after the organic solvent is completely volatilized to obtain the long-chain branched polypropylene.

[0048] As a specific implementation manner, the organic solvent is acetone, and the volume ratio of the total mass of trimethylolpropane trimethacrylate, alkyl mercaptan and initiator to acetone is 25-35g:100mL.

[0049] As a specific implementation manner, in step (2), the extrusion temperature of the three-layer co-extrusion is 200-240° C., the cooling temperature is 80-100° C., and the pulling speed is 40-80 m / min.

[0050] As a specific implementation manner, the heat treatment temperature in step (3) is 110-150°C, the heat treatment time is 10-30h, the longitudinal cold stretching temperature is 50-100°C, the stretching ratio is 1.2-1.5, the longitudinal hot stretching temperature is 140-170°C, the stretching ratio is 1.5-3.0, the heat setting temperature is 130-140°C, the stretching ratio is 0.8-1, and the heat setting time is 1-10min.

[0051] Embodiment 1:

[0052] A high-porosity dry-process separator for lithium-ion batteries, with an A / B / A three-layer symmetrical structure and a total thickness of 18 μm; the thickness of the two A layers is 3.6 μm each, and the thickness of the B layer is 10.8 μm;

[0053] In parts by weight, the raw materials of layer A include: 95 parts of long-chain branched polypropylene, 1 part of dimethyl diphenyl bisaminomethane, and 4 parts of polyurethane powder (Bayer 1195A, Germany, particle size 200 μm);

[0054] The raw materials of layer B include: 95 parts of maleic anhydride modified high crystallinity polypropylene, 1 part of hydroxyphenol phosphate, and 4 parts of glass fiber (diameter 15 nm, length 200 nm).

[0055] The above-mentioned method for preparing the high-porosity dry-process diaphragm for lithium-ion batteries comprises the following steps:

[0056] (1) Preparation of long-chain branched polypropylene: 30 g of trimethylolpropane trimethacrylate, dibenzoyl peroxide and dodecyl mercaptan were weighed in a mass ratio of 1:1:1, dissolved in 100 mL of acetone and mixed evenly, and then evenly sprayed on the surface of 100 g of PP pellets (Daehan Petrochemical CB5230, weight average molecular weight 120,000), dried in a 60°C oven for 1 h, and after the acetone was completely volatilized, put it into a HAAKE torque rheometer for melt polymerization to obtain the long-chain branched polypropylene; the rotor speed of the HAAKE torque rheometer was 60 r / min, the temperatures of the first zone, the second zone and the third zone were 175°C, 175°C and 180°C respectively, and the total reaction time was 12 min;

[0057] (2) Preparing maleic anhydride modified high crystallinity polypropylene: drying maleic anhydride and high crystallinity polypropylene (weight average molecular weight 150,000, crystallinity 65%), then adding the dried high crystallinity polypropylene into a twin-screw extruder, and adding the dried maleic anhydride and free radical initiator di-tert-butyl peroxide, the mass ratio of the added maleic anhydride to the high crystallinity polypropylene being 1:100; the amount of the added free radical initiator being 5% of the total mass of the maleic anhydride and the high crystallinity polypropylene; and obtaining the maleic anhydride modified high crystallinity polypropylene after melt extrusion granulation;

[0058] (3) Casting: Long-chain branched polypropylene, dimethyl diphenyl bisaminomethane and polyurethane powder are measured by electronic scale, mixed in a mixing bin and then put into a first twin-screw extruder; maleic anhydride-modified high-crystallinity polypropylene, hydroxide phenol phosphate and glass fiber are measured by electronic scale, mixed in a mixing bin and then put into a second twin-screw extruder; the extrusion volume ratio of the first twin-screw extruder and the second twin-screw extruder is set to 4:6, the extruder temperature is adjusted to 210°C, and after melting, the material extruded by the first twin-screw extruder is filtered as the surface layer, and the material extruded by the second twin-screw extruder is used as the middle layer, and the material is extruded through a multi-layer co-extrusion three-layer die head in-die composite extrusion; the melt extruded through the die head is cooled at a temperature of 100°C, and pulled at a pulling speed of 60m / min to obtain a three-layer composite casting sheet;

[0059] (4) Stretching to form a film: The cast sheet obtained in step (3) is heat treated at a temperature of 135°C for 18 hours; then the heat treated cast sheet is firstly cold stretched longitudinally at a temperature of 85°C with a stretching ratio of 1.2, and then hot stretched longitudinally at a temperature of 140°C with a stretching ratio of 2.0, and then heat set at a temperature of 140°C with a heat setting time of 4 minutes and a heat setting stretching ratio of 0.98, thereby obtaining the high porosity dry-process diaphragm.

[0060] Embodiment 2:

[0061] The difference between Example 2 and Example 1 is that the raw materials of layer A include 90 parts of long-chain branched polypropylene, 1 part of phenylacetone, and 9 parts of polyurethane powder;

[0062] The preparation method of long-chain branched polypropylene is as follows: 30 g of trimethylolpropane trimethacrylate, dibenzoyl peroxide and dodecyl mercaptan are weighed in a mass ratio of 2:1:1, dissolved in 100 mL of acetone and mixed evenly, and then evenly sprayed on the surface of 100 g of PP pellets (Daehan Petrochemical CB5230, weight average molecular weight 120,000), dried in an oven at 60°C for 1 hour, and after the acetone is completely volatilized, put it into a HAAKE torque rheometer for melt polymerization to obtain the long-chain branched polypropylene; the rotor speed in the HAAKE torque rheometer is 60 r / min, the temperatures of the first zone, the second zone and the third zone are 175°C, 175°C and 180°C respectively, and the total reaction time is 12 min;

[0063] The rest are the same as in Example 1.

[0064] Embodiment 3:

[0065] The difference between Example 3 and Example 1 is that the raw materials of layer A include 80 parts of long-chain branched polypropylene, 10 parts of terephthalimide, and 10 parts of polyurethane powder;

[0066] The preparation method of long-chain branched polypropylene is as follows: 30 g of trimethylolpropane trimethacrylate, dibenzoyl peroxide and dodecyl mercaptan are weighed in a mass ratio of 1:1:2, dissolved in 100 mL of acetone and mixed evenly, and then evenly sprayed on the surface of 100 g of PP pellets (Daehan Petrochemical CB5230, weight average molecular weight 120,000), dried in an oven at 60°C for 1 hour, and after the acetone is completely volatilized, put it into a HAAKE torque rheometer for melt polymerization to obtain the long-chain branched polypropylene; the rotor speed in the HAAKE torque rheometer is 60 r / min, the temperatures of the first zone, the second zone and the third zone are 175°C, 175°C and 180°C respectively, and the total reaction time is 12 min;

[0067] The rest are the same as in Example 1.

[0068] Embodiment 4:

[0069] The difference between Example 4 and Example 1 is that the raw materials of layer A include 95 parts of long-chain branched polypropylene, 4 parts of dimethyl diphenyl bisaminomethane, and 1 part of polyurethane powder, and the rest are the same as in Example 1.

[0070] Embodiment 5:

[0071] The difference between Example 5 and Example 1 is that the raw materials of layer B are 95 parts of maleic anhydride-modified high-crystallinity polypropylene, 4 parts of silicon dioxide (particle size 100 μm), and 1 part of glass fiber;

[0072] The preparation method of maleic anhydride modified high crystallinity polypropylene is as follows: maleic anhydride and high crystallinity polypropylene (weight average molecular weight 150,000, crystallinity 65%) are dried, and then the dried high crystallinity polypropylene is added into a twin-screw extruder, and the dried maleic anhydride and free radical initiator di-tert-butyl peroxide are added, the mass ratio of the added maleic anhydride to the high crystallinity polypropylene is 2:100; the amount of the added free radical initiator is 5% of the total mass of the maleic anhydride and the high crystallinity polypropylene; the maleic anhydride modified high crystallinity polypropylene is obtained after melt extrusion granulation;

[0073] The rest are the same as in Example 1.

[0074] Embodiment 6:

[0075] The difference between Example 6 and Example 1 is that the raw materials of layer B are 90 parts of maleic anhydride-modified high-crystallinity polypropylene, 4 parts of talc (particle size 100 μm), and 6 parts of glass fiber;

[0076] The preparation method of maleic anhydride modified high crystallinity polypropylene is as follows: maleic anhydride and high crystallinity polypropylene (weight average molecular weight 150,000, crystallinity 65%) are dried, and then the dried high crystallinity polypropylene is added into a twin-screw extruder, and the dried maleic anhydride and free radical initiator di-tert-butyl peroxide are added, the mass ratio of the added maleic anhydride to the high crystallinity polypropylene is 3:100; the amount of the added free radical initiator is 5% of the total mass of the maleic anhydride and the high crystallinity polypropylene; the maleic anhydride modified high crystallinity polypropylene is obtained after melt extrusion granulation;

[0077] The rest are the same as in Example 1.

[0078] Embodiment 7:

[0079] The difference between Example 7 and Example 1 is that the raw materials of layer B are 80 parts of maleic anhydride modified high crystallinity polypropylene, 10 parts of hydroxylated phenol phosphate, and 10 parts of glass fiber, and the rest are the same as in Example 1.

[0080] Comparative Example 1:

[0081] The difference between Comparative Example 1 and Example 1 is that no dimethyl diphenyl bisaminomethane is added to the A layer, the raw materials of the A layer only include 95 parts of long-chain branched polypropylene and 4 parts of polyurethane powder, and the rest are the same as in Example 1.

[0082] Comparative Example 2:

[0083] The difference between Comparative Example 2 and Example 1 is that no polyurethane powder is added to the A layer, the raw materials of the A layer only include 95 parts of long-chain branched polypropylene and 1 part of dimethyldiphenylbisaminomethane, and the rest are the same as in Example 1.

[0084] Comparative Example 3:

[0085] The difference between Comparative Example 3 and Example 1 is that no hydroxyphenol phosphate is added to the B layer, the raw materials of the B layer only include 95 parts of maleic anhydride-modified high-crystallinity polypropylene and 4 parts of glass fiber, and the rest are the same as in Example 1.

[0086] Comparative Example 4:

[0087] The difference between Comparative Example 4 and Example 1 is that no glass fiber is added to the B layer, the raw materials of the B layer only include 95 parts of maleic anhydride-modified high-crystallinity polypropylene and 1 part of hydroxyphenol phosphate, and the rest are the same as in Example 1.

[0088] Comparative Example 5:

[0089] The difference between Comparative Example 5 and Example 1 is that, by weight, the raw materials of layer B include: 95 parts of long-chain branched polypropylene (the same as in layer A), 1 part of hydroxide phenol phosphate, and 4 parts of glass fiber; the remaining components and preparation methods are the same as in Example 1.

[0090] Comparative Example 6:

[0091] The difference between Comparative Example 6 and Example 1 is that, in parts by weight, the raw materials of layer A include: 95 parts of maleic anhydride-modified high-crystallinity polypropylene (the same as in layer B), 1 part of dimethyldiphenylbisaminomethane, and 4 parts of polyurethane powder; the remaining components and preparation methods are the same as those in Example 1.

[0092] Comparative Example 7:

[0093] The difference between Comparative Example 7 and Example 1 is that the nucleating agent a in layer A is calcium suberate, and the other components and preparation methods are the same as those in Example 1.

[0094] Comparative Example 8:

[0095] The difference between Comparative Example 8 and Example 1 is that the nucleating agent b in layer B is dehydroabietic acid, and the other components and preparation methods are the same as those in Example 1.

[0096] Comparative Example 9:

[0097] The difference between Comparative Example 9 and Example 1 is that the raw materials of layer A include: 95 parts of polypropylene (Korea Petrochemical CB5230, weight average molecular weight 120,000), 1 part of dimethyldiphenylbisaminomethane, and 4 parts of polyurethane powder; the remaining components and preparation methods are the same as those in Example 1.

[0098] Comparative Example 10:

[0099] The difference between Comparative Example 10 and Example 1 is that the raw materials of layer B include: the raw materials of layer B include: 95 parts of high crystallinity polypropylene (weight average molecular weight 150,000, crystallinity 65%), 1 part of hydroxide phenol phosphate, and 4 parts of glass fiber; the remaining components and preparation methods are the same as those in Example 1.

[0100] The high-porosity dry-process diaphragms prepared in the above-mentioned embodiments and comparative examples were cut into A4 size, and various mechanical properties and thermal properties were tested. The results are shown in Table 1.

[0101] The test items and methods are as follows:

[0102] (1) Average thickness: Use a micrometer to measure the thickness of high-porosity dry-process diaphragms at different locations and calculate the average value.

[0103] (2) Tensile strength: The longitudinal and transverse tensile strength of the high-porosity dry-process diaphragm were tested using the CTM universal testing machine. Five specimens were tested in each direction and the average value was calculated.

[0104] (3) Puncture strength: The puncture strength of high-porosity dry-process diaphragm was tested using the Xieqiang CTM universal testing machine. Five specimens were tested and their average value was calculated.

[0105] (4) Porosity: Use an analytical balance to measure the mass of a 10 cm × 10 cm sample and calculate the porosity of the high-porosity dry-process diaphragm. Test five samples and calculate the average value.

[0106] (5) Membrane rupture temperature: Use a hot stage microscope to test the membrane rupture temperature of the high porosity dry-process membrane. Record the temperature when the membrane begins to melt. Test 5 samples and calculate the average value.

[0107] (6) Air permeability: Use an air permeability tester to test the air permeability of high-porosity dry-process diaphragm. Test 5 samples and calculate the average value.

[0108] (7) Liquid absorption rate: The liquid absorption rate of high-porosity dry-process diaphragms is tested by weighing method. First, the mass of the diaphragm is recorded after it is completely dried. Then, the completely dried diaphragm is immersed in electrolyte for 24 hours. After the surface electrolyte is wiped dry, the weight of the diaphragm is recorded again. The difference between the two records is the liquid absorption rate of the diaphragm. Test 5 samples and calculate the average value.

[0109] Table 1: High porosity dry-process diaphragm performance test results

[0110]

[0111] It can be seen from the results in Table 1 that the high-porosity dry-process diaphragms prepared using the formula and method of the present invention in Examples 1 to 7 all exhibit good various properties. At the same time, Examples 3 and 5 slightly sacrifice puncture strength in exchange for a larger porosity and a larger liquid retention rate, which can bring better ion transmission performance, indicating that the amount of nucleating agent used can significantly affect the porosity of the diaphragm and the performance of the final product.

[0112] In Comparative Examples 1 and 3, no nucleating agent is added to the surface layer or the middle layer, and the porosity and liquid absorption rate of the diaphragm are affected more obviously; in Comparative Example 2, no polyurethane powder is added to the surface layer, and in Comparative Example 4, no glass fiber is added to the middle layer, and the puncture resistance of the final product is reduced.

[0113] In Comparative Example 5, both the surface layer and the middle layer use long-chain branched polypropylene as the matrix resin. Although the porosity is further increased, it is obvious that the mechanical properties are greatly sacrificed, which does not meet the use requirements of the product. In Comparative Example 6, both the surface layer and the middle layer use maleic anhydride-modified high-crystallinity polypropylene as the matrix resin. Although the puncture resistance of the diaphragm is significantly improved, this is at the expense of the porosity and liquid retention rate of the diaphragm, which has a greater impact on the performance of the final assembled battery.

[0114] In Comparative Examples 7 and 8, the types of nucleating agents in the surface layer and the middle layer are changed, and the nucleating agents do not match the base resin used in the present invention, resulting in poor nucleating effect, resulting in low porosity of the diaphragm.

[0115] In the surface layer of Comparative Example 9, polypropylene without long-chain branching is used as the matrix. Due to the lack of long-chain branching, polypropylene is difficult to process, resulting in poor film-forming properties and low porosity of the diaphragm. In the middle layer of Comparative Example 10, high-crystallinity polypropylene without maleic anhydride grafting is used as the matrix. Due to the lack of sufficient strength in the middle layer, the mechanical properties of the diaphragm are poor, and there are great risks in its use.

[0116] The above is only a preferred embodiment of the present invention and is not intended to limit the protection scope of the present invention. All equivalent changes and modifications made according to the content of the present invention are included in the patent scope of the present invention.

Claims

1. A high porosity dry-process diaphragm for lithium-ion batteries, characterized in that: Adopt A / B / A three-layer symmetrical structure; In parts by weight, the raw materials of layer A include: 80-95 parts of long-chain branched polypropylene, 1-10 parts of nucleating agent a, and 4-10 parts of polyurethane powder; the raw materials of layer B include: 80-95 parts of high-crystallinity polypropylene modified with maleic anhydride, 1-10 parts of nucleating agent b, and 4-10 parts of glass fiber; In the high-crystallinity polypropylene modified with maleic anhydride, the mass ratio of maleic anhydride to high-crystallinity polypropylene is 1-5:100, and the crystallinity of the high-crystallinity polypropylene is 60-70%. The nucleating agent a is selected from one or two of styrene, terephthalimide; the nucleating agent b is selected from one or more of talc, silica, nanoclay, and sorbitol acetal; The long-chain branched polypropylene is prepared by melt polymerization of trimethylolpropane trimethacrylate, alkyl mercaptan, initiator and polypropylene, the mass ratio of trimethylolpropane trimethacrylate, alkyl mercaptan and initiator is 1-2:1-2:1, the mass ratio of the total mass of trimethylolpropane trimethacrylate, alkyl mercaptan and initiator to polypropylene is 25-35:100; the weight average molecular weight of polypropylene is 100,000-150,000.

2. The high-porosity dry-process diaphragm for lithium-ion batteries according to claim 1, characterized in that: The alkyl mercaptan is selected from one or more of n-butyl mercaptan, 2,3-butanedithiol, 1,8-octanedithiol, cyclohexanethiol, dodecyl mercaptan, and n-tetradecyl mercaptan; and the initiator is dibenzoyl peroxide.

3. The high-porosity dry-process diaphragm for lithium-ion batteries according to claim 1 or 2, characterized in that: The particle size of the polyurethane powder is 150-250 μm.

4. The high-porosity dry-process diaphragm for lithium-ion batteries according to claim 1, characterized in that: The thickness is 12~25μm, the thickness of layer A is 20~30% of the total thickness, and the thickness of layer B is 40~60% of the total thickness.

5. The high-porosity dry-process diaphragm for lithium-ion batteries according to claim 1 or 4, characterized in that: The porosity is 60~70%, the air permeability is not more than 230 s / 100mL, the puncture performance is greater than 600gf, the tensile strength in the MD direction is greater than 200MPa, and the tensile strength in the TD direction is greater than 20MPa.

6. A method for preparing a high-porosity dry-process diaphragm for lithium-ion batteries according to any one of claims 1 to 5, characterized in that: The steps include: (1) Preparation of long-chain branched polypropylene and high-crystalline polypropylene modified with maleic anhydride; (2) Casting sheet: The raw materials of the surface layer and the middle layer are mixed in proportion and then subjected to three-layer co-extrusion, and then pulled and cooled to obtain a casting sheet; (3) Stretching film formation: The obtained cast sheet is subjected to heat treatment, longitudinal cold stretching, longitudinal hot stretching, and heat setting in sequence to obtain the high-porosity dry-process diaphragm for lithium-ion batteries.

7. The preparation method according to claim 6, characterized in that: The method for preparing the maleic anhydride modified high crystallinity polypropylene in step (1) is: melt-extrude maleic anhydride, high crystallinity polypropylene and a free radical initiator to obtain the maleic anhydride modified high crystallinity polypropylene; The preparation method of long-chain branched polypropylene is as follows: trimethylolpropane trimethacrylate, alkyl mercaptan and initiator are mixed and dissolved in an organic solvent, and then evenly sprayed on the surface of polypropylene pellets; the polypropylene pellets are dried, and melt polymerization is performed after the organic solvent is completely volatilized to obtain the long-chain branched polypropylene.

8. The preparation method according to claim 6, characterized in that: In step (2), the extrusion temperature of the three-layer co-extrusion is 200-240°C, the cooling temperature is 80-100°C, and the pulling speed is 40-80 m / min.

9. The preparation method according to claim 6, characterized in that: The heat treatment temperature of step (3) is 110-150°C, the heat treatment time is 10-30h, the longitudinal cold stretching temperature is 50-100°C, the stretching ratio is 1.2-1.5, the longitudinal hot stretching temperature is 140-170°C, the stretching ratio is 1.5-3.0, the heat setting temperature is 130-140°C, the stretching ratio is 0.8-1, and the heat setting time is 1-10min.

Citation Information

Patent Citations

  • High-porosity sodium-ion battery tensile diaphragm and preparation method thereof

    CN116387757A

  • Composite polypropylene microporous membrane, and preparation method and application thereof

    CN109422890A

  • Method for preparing composite polypropylene microporous membrane through interfacial polymerization method, and products and application of composite polypropylene microporous membrane

    CN110343279A